2021
DOI: 10.1186/s42774-021-00081-y
|View full text |Cite
|
Sign up to set email alerts
|

A decomposition formula for the wall heat flux of a compressible boundary layer

Abstract: Understanding the generation mechanism of the heat flux is essential for the design of hypersonic vehicles. We proposed a novel formula to decompose the heat flux coefficient into the contributions of different terms by integrating the conservative equation of the total energy. The reliability of the formula is well demonstrated by the direct numerical simulation results of a hypersonic transitional boundary layer. Through this formula, the exact process of the energy transport in the boundary layer can be exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Here N x , N y and N z are the grid resolutions along the streamwise, wall-normal and spanwise directions, respectively. The ending streamwise location of the fully developed region shown in figure 1 It is noted that the minimum streamwise non-dimensionalised computational domain size of our numerical simulations is comparable to those in most other previous investigations, including Duan et al (2010), Wenzel et al (2021a) and Sun et al (2021). Therefore, the streamwise computational domain sizes are large enough to make the compressible boundary layers evolving to the fully developed state.…”
Section: Governing Equations and Simulation Parameterssupporting
confidence: 72%
See 3 more Smart Citations
“…Here N x , N y and N z are the grid resolutions along the streamwise, wall-normal and spanwise directions, respectively. The ending streamwise location of the fully developed region shown in figure 1 It is noted that the minimum streamwise non-dimensionalised computational domain size of our numerical simulations is comparable to those in most other previous investigations, including Duan et al (2010), Wenzel et al (2021a) and Sun et al (2021). Therefore, the streamwise computational domain sizes are large enough to make the compressible boundary layers evolving to the fully developed state.…”
Section: Governing Equations and Simulation Parameterssupporting
confidence: 72%
“…(2021 a ) and Sun et al. (2021). Therefore, the streamwise computational domain sizes are large enough to make the compressible boundary layers evolving to the fully developed state.…”
Section: Governing Equations and Simulation Parametersmentioning
confidence: 95%
See 2 more Smart Citations
“…Their formula was based on the internal energy equation and the numerical result showed that the contribution from the viscous stress work dominates the main contributions (around 90%) to wall heat flux. More recently, another formula on the wall heat flux was derived by Sun et al 29 for the compressible boundary layer following the idea of the RD decomposition. The formula was started with the total energy equation, and their numerical results showed that Reynolds stress transport term contributes a lot to q w which is in sharp contrast to the results obtained in Zhang and Xia 28 .…”
Section: Introductionmentioning
confidence: 99%